Clinical efficacy of Gojihvadi Kwath, Shirishadi Kwath, Sanjeevani Vati, Panchagavya Ghrita Granules & Shunthi Churna for COVID-19 management, a randomized controlled trial - Byadgi P.S.; Kumari M.; Singh V.; Dwivedi A.K.; Mishra S.K.; Dubey S.K.; Chaudhary A.K.; Chaurasia R.N.; Joshi N.; Jani H.; Mishra R.K.; Singh T.B.; Arunima P.S.; Jayakumar R. (My University, 2025)
The obscure disease pattern of COVID-19 have to be evaluated with Ayurvedic interventions and the present clinical trial was a randomized open label parallel three-arm control trial on the major and minor symptomatic patients with the recent pandemic. The patients were recruited from the Super specialty building of Sir Sunderlal hospital, COVID-19 ward and home isolated ones. The Ayurvedic intervention includes the 15 days oral administration (Group A) –Gojihvadi Kwath, Sanjeevani Vati; Panchagavya Ghrit Granules; Shunthi (Dry ginger powder) plus conventional treatment, in (Group B) – Shirishadi Kwath, Sanjeevani Vati; Panchagavya Ghrit Granules; Shunthi (Dry ginger powder) plus conventional treatment and in Group C (control group) only the conventional medicines. Assessment was done based on the RT-PCR reports, signs and symptoms. The results point out the efficacy of trial medicine (that is group A and B) to discharge the patients earlier than those from the control group. The early reduction in the signs and symptoms noted were also observed. Group B showed a faster recovery from dry cough and shortness of breath and improvement in appetite. Home-isolation patients showed faster recovery of clinical symptoms than the hospitalized patients. Ayurvedic interventions can accelerate viral load clearance associated with quicker recovery and concurrently decrease the risk of viral dissemination. Additionally, there were no adverse reactions observed with these trial medicines. © 2024, National Institute of Science Communication and Policy Research. All rights reserved.